EPROVEMENTS OF THE FINANCIAL MARKET DEVELOPMENT OF UKRAINE IN DIGITAL CONDITIONS (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. The digital economy has a key place in the evolution of finance and the development of financial markets. Yes, innovations in the field of payment systems have influenced the process of dematerialization of money, which now itself takes the form of digital flows through computer networks.The purpose of the article. The purpose of the article is  to evaluate the development of the domestic financial market in the face of increased processes of digitization and digitization.Results. The proliferation of digital technology over a long period determines the trajectory of economic and social development, and has repeatedly led to dramatic changes in people's lives. At the same time, becoming a digital economy is one of the priority areas for most economic leaders, including the United States, the United Kingdom, Germany and Japan, which Ukraine should also strive for.At the same time, for the development of financial markets in the context of digitalization, regulators will work on completing currency liberalization, creating liquid markets for financial instruments (derivatives, corporate stocks and bonds, etc.), deregulating markets for low-risk or non-banking financial services, which do not comply with EU practices, regulation of insurance activities in accordance with Solvency II and IAIS principles, ensuring legal regulation of insurance intermediaries, creating at the legislative level necessary prerequisites for the development of credit unions markets and financial leasing services, modernization of stock exchange and depository infrastructure, creation of a comprehensive stock market monitoring information system, application of international standards of capital markets functioning.Conclusions. In Ukraine, the development of digital technologies in various segments of the financial market activity is of great importance. in official documents, targeted government programs, business analytics and business practices. All this actualizes the study of the problem of financial market development in the conditions of digitalization.
Keywords: financial market, financial technologies, digitalization, digital technologies, financial market business models, Fintech